EXAMINING THE INFLUENCE OF TIKTOK ON ANOREXIA NERVOSA: A SOCIAL MEDIA PERSPECTIVE - LITERATURE REVIEW - Oliwia Krzemień; Kinga Kosiec; Natalia Karpowicz; Natalia Pacocha; Julia Kaszucka; Justyna Popczyńska; Agnieszka Raczyńska; Małgorzata Krzyżanowska; Marta Zgierska; Jakub Jędrychowski (International Journal of Innovative Technologies in Social Science, 2024)
Anorexia nervosa (AN) is a condition classified as an eating disorder that is characterised by a distorted perception of the image of the body. This leads to pathological behaviour caused by the fear of gaining weight. AN has the highest mortality rate of any psychiatric disorder and many starvation-related complications. The incidence of AN appears to be stable, but is increasing in younger patients, especially those under the age of 15. Given the global popularity of the mobile application TikTok, especially among adolescents, we conducted a literature review to examine the impact of this application on anorexia. Research indicates that the use of the TikTok application does affect self-perception. Despite the application’s ban on content related to eating disorders, it is still possible to find and interact with such material. There are communities on the platform that support each other in recovery, as well as in persevering through the illness. The work highlights the complexity of the problem.